Analysis Of Digital Platforms Providing 100% Digital Financial Services To The User in Cartagena - Martinez-Aparicio, Melissa (EFIM Ediciones, 2023)
The main objective of this article is to analyze the digital platforms that provide the user with 100% digital financial services. Through a systematization of literature where first the characteristics of the digital platforms currently operating in Colombia are determined, after that, the perspectives of the users on the conventional digital services of the banks to which they belong are disclosed and finally The impact of digitization on financial services is analyzed. This article is based on a mixed methodology that combines the collection of quantitative and qualitative data to analyze the impact of digitalization in financial services. In the first place, a qualitative analysis is carried out because the existing and current platforms that operate with a 100% digital service to the consumer will be characterized first. In addition to this, the perspective of users on financial services on 100% digital platforms will be known. Finally, the impact that such a service would generate in the provision of services to the consumer will be analyzed.